A concise total synthesis of hymenialdisine. Issue 23 (3rd June 2015) - Saleem, Rahman Shah Zaib; J. Tepe, Jetze
Graphical abstract: Abstract: The synthesis of hymenialdisine has offered challenges that included the formation of the regio-isomers upon monobromination, atom-scrambling in the cyclization step, and low to moderate yields in the last steps. We herein present a short and concise (6 overall steps), high yielding route (44% overall yields) for this biologically interesting natural product that addresses these issues and avoids the use of any protecting groups.